1991
DOI: 10.2508/chikusan.62.667
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heparin Supplementation into the Culture Medium on the Chromosomal Analysis of Bovine Blastocysts Derived from in vitro Fertilization

Abstract: Effects of the dose of heparin on the a, b: Values with diffe rent superscript letters were significantly different at the 5% level within c, d: Values with different superscript letters were significantly different at the 1% level within number of metaphase plates and on the sexing rates. for 2 h. SD). same stage. same stage. 713-717. 1972. 19) LARSON, R. C., G. G. IGNOTZ and W. B. CURRIE, Development of in vitro fertilized bovine embryos beyond the 8-cell block using completely defined medium containing fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The tendency of male advantage in diploid embryos compared with those found by some other researchers [17,20], although Kajihara et al [5] and Tokumaru et al [16] found a tendency toward This embryo was treated with vinblastine (100 ng/ ml) for 10 h. female advantage.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The tendency of male advantage in diploid embryos compared with those found by some other researchers [17,20], although Kajihara et al [5] and Tokumaru et al [16] found a tendency toward This embryo was treated with vinblastine (100 ng/ ml) for 10 h. female advantage.…”
Section: Discussionmentioning
confidence: 62%
“…In investigations of chromosomes, with various mitotic inhibitors, many researchers have used short treatment times for bovine embryos fertilized in vitro. King et al [15] have described a method for preparing chromosomes from bovine blastocysts using 200 µg/ ml colchicine for 2 to 9.5 h. They have shown the mitotic indexes to be 14.7-37.5% in morphologically good blastocysts treated for 8.5-9.5 h, and 4.2-14.3% in embryos treated for 2-4 h. Kajihara et al [5] have reported frequencies of bovine embryos having metaphase plates of approximately 80-83%, and the sexing rate of 63.4% in embryos treated with 0.04 µg/ml colcemid for 1.5-3 h. Tokumaru et al [16] have also reported mitotic indexes of about 5-7% in bovine blastocysts treated with 0.04 µg/ml colcemid for 2 h. Avery et al [17] have shown a low mitotic index of 3.5%, in bovine in-vitro fertilized blastocysts treated with 0.01 µg/ml colcemid for 2 h. Iwasaki et al have reported mitotic indexes of approximately 5 to 12% in bovine blastocysts treated for 4 h with a combination of vinblastine sulfate and podophyllotoxin [7], and a mitoic index of approximately 26% in morulae or blastocysts treated for 6 h with 0.4 µg/ ml vinblastine sulfate [8]. If the treatment time is longer, the mitotic index is higher.…”
Section: Discussionmentioning
confidence: 99%